Tension between Private and Public Sphere in Saving Ecology: State, Companies and Indigenous Women - Donny Danardono (Yayasan Jurnal Perempuan, 2014)
This paper examines the tension between private and public sphere in deciding women’s role against ecological crisis. State, companies, traditional tribe-based women alliance, village women have their own perception and definition in projecting to save the ecology. Private sphere is where women construct their identity, transmitted ecological spirit to their children, according their phantasy of beauty and fashion based on ecological-friendly product, etc. Public sphere is where women campaign explicitly against company that destroy their environment as form of ecological and gender injustice. The urge to protect the ecology, for women, means the dealing of the tension between domestic and public spheres.